CONCEPTS OF AUDIT CONTROL OF FINANCIAL RESULTS AND THEIR ACCOUNTING SUPPORT - Vasylyuk М.М.; Yurkiv А.R. (The actual problems of regional economy development, 2025)
The article examines the conceptual aspects of the formation of financial results in accounting and their audit. The aspects of accounting and auditing of the financial results of an enterprise, which are the foundation for strategic planning and management decision-making, are investigated. The regulatory approaches to the formation of financial results are analyzed, including international and national financial reporting standards. Special attention is given to the methods for calculating financial results, with the most common being the "cost-output" method and the comparison of income and expenses. The evaluation of financial results allows for assessing the efficiency of the enterprise's operations, identifying weaknesses, and developing strategies to improve performance. The aim of the article is to examine the specifics of accounting support and audit control in the formation of financial results. To achieve this goal, the following tasks were set: analysis of the key approaches to the formation of financial results of enterprises in line with international and national standards; evaluation of accounting methods and procedures used to determine financial results; analysis of the stages of auditing financial results and assessing their impact on the financial stability and solvency of enterprises. An important part of the article is the analysis of the process of auditing financial results. The stages of audit organization are considered, including the organizational, preparatory, technological, and final stages of the financial results verification process. Emphasis is placed on the necessity of detailed planning of audit procedures to ensure the accuracy of financial reporting and the timely fulfillment of tax obligations. Attention is drawn to the importance of identifying potential errors and instances of fraud in accounting data, which could negatively impact the stability of the enterprise's operations. The article emphasizes the importance of financial results as a tool for effective enterprise management and the role of auditing in ensuring the transparency and reliability of financial information. Accurate accounting and auditing of financial results are crucial for enhancing the efficiency of enterprises and maintaining their stability in a competitive environment.